THE APPLICATION OF INQUIRY LEARNING MODEL TO IMPROVE â€œSATU ATAPâ€ STUDENTSâ€™ LEARNING RESULTS AT SMPN 4 SINGOSARI MALANG - Setiawan, B.; Sunarti, T.; Astriani, D. (Jurnal Pendidikan IPA Indonesia, 2016)
The implementation of the learning device with inquiry learning model into a developed model and tested in the learning process in elementary and junior high school â€œSatu Atapâ€ 4 Singosari Malang. This type of research is done through experimentation with pre-experimental design that is implemented by the design of one group pretest and posttest design. The trial results with the learning device guided by inquiry learning model at the elementary-SMPN 4 â€œSatu Atapâ€ Singosari Malang shows that the activities carried out as many as four meetings run according to the lesson plans have been made. Learning by using inquiry model on electric material can be accomplished through: 1. Identification of question / formulate problem with the average score 3:38 (pretty good), step 2. Formulate a hypothesis with an average score of 3:25 (pretty good), step 3. Designing and observation/ experiment with an average score of 3:50 (well), step 4. Collecting and analyzing the data with an average score of 3:38 (pretty good), and step 5. Drawing conclusions/ generalizations with an average score of 3:38 (pretty good). Learning models for additives substance material with step 1. Identify the question / formulate the problem got an average score of 3:13 (pretty good), step 2. Formulate a hypothesis to get an average score 3:13 (pretty good), step 3. Designing and making observations / experiment with an average score of 3:38 (pretty good), step 4. Collecting and analyzing the data with an average score of 3:25 (pretty good), and step 5. Drawing conclusions / generalizations with an average score of 3:50 (well). The studentsâ€™ learning outcomes using inquiry learning model covers aspects of knowledge, skills and attitudes obtained as follows: the aspect of knowledge through the pretest and posttest on the matter of electricity has increased the average percentage score from 42.6 on the pretest become 67.7 with an average score of N-Gain 0.44 in the medium category, while the knowledge aspect of learning outcomes on additive substance material has increased the average percentage of the score from 42.6 to 82.2 in pretest and posttest with an average score of N-Gain 0.69 in the medium category. The skill aspects on electricity material get the highest score in the predicate B +, while the highest score of additive substance material on the predicate A-, as well as attitudes aspects shows that more than 50% students show a good attitude during the learning process, ie 67% on the electricity material and 80% on the additives substance material.